Global Social Work Cutting Edge Issues and Critical Reflections - Raju Nikku, Bala (IntechOpen, 2020)
This edited book, Global Social Work - Cutting Edge Issues and Critical Reflections, presents global social work expertise, practical tools, and an iterative and reflective process for developing a global social work pedagogy that advances deep disciplinary learning. The authors offer the specifics of a justice based, decolonizing global social work education and practice. This book will be an asset to faculty communities interested in specializing in global social work. The book offers hope that the faculty, students, and practitioners of social work develop an intercultural, international, cross-border critical approach that further prepares them to meet the global standards of social work education and research and at the same time skillfully act, advocate, and transform global communities and their role in a globalized world.